2007
DOI: 10.1016/j.physletb.2007.06.082
|View full text |Cite
|
Sign up to set email alerts
|

The 4He total photo-absorption cross section with two- plus three-nucleon interactions from chiral effective field theory

Abstract: The total photo-absorption cross section of 4 He is evaluated microscopically using two-(NN) and three-nucleon (NNN) interactions based upon chiral effective field theory (χEFT). The calculation is performed using the Lorentz integral transform method along with the ab initio no-core shell model approach. An important feature of the present study is the consistency of the NN and NNN interactions and also, through the Siegert theorem, of the two-and three-body current operators. This is due to the application o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 52 publications
(63 reference statements)
7
92
1
Order By: Relevance
“…We note that 4 He results obtained with the identical Hamiltonian but with c D = −1 and c E = −0.331 are presented in Ref. [17]. We use the Jacobi coordinate HO basis antisymmentrized according to the method described in Ref.…”
Section: Convergence Test For 3 H and 4 Hementioning
confidence: 99%
See 2 more Smart Citations
“…We note that 4 He results obtained with the identical Hamiltonian but with c D = −1 and c E = −0.331 are presented in Ref. [17]. We use the Jacobi coordinate HO basis antisymmentrized according to the method described in Ref.…”
Section: Convergence Test For 3 H and 4 Hementioning
confidence: 99%
“…In that study, a preferred choice of the two NNN LECs, c D and c E , was found and the fundamental importance of the χEFT NNN interaction was demonstrated for reproducing the structure of mid-p-shell nuclei. In a subsequent study, the same Hamiltonian was used to calculate microscopically the photo-absorption cross section of 4 He [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the exclusive case, the total, i.e., inclusive cross section of 4 He photoabsorption has already been calculated with state-of-the-art nuclear forces, including three-nucleon forces (3NF), of either a phenomenological type [8] or from a chiral perturbation effective field theory (χEFT) [9]. These two calculations, which also utilize the UDA, are in excellent agreement with one another, and in reasonable agreement with the majority of experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…We choose the total dipole strength because it is used to compute important quantities such as photo-absorption cross sections [31] and electric polarizabilities [27]. Our second investigation focuses on operator renormalization as a function of range, following a prescription similar to that of Ref.…”
mentioning
confidence: 99%